Anti-FHL1 autoantibodies in juvenile myositis are associated with anti-Ro52 autoantibodies but not with severe disease features. (12th August 2022) - Sherman, Matthew A; Graf, Rose; Sabbagh, Sara E; Galindo-Feria, Angeles S; Pinal-Fernandez, Iago; Pak, Katherine; Kishi, Takayuki; Flegel, Willy A; Targoff, Ira N; Miller, Frederick W; Lundberg, Ingrid E; Rider, Lisa G; et al.
Abstract: Objectives: Four-and-a-half LIM domains 1 (FHL1) is a muscle-specific protein. Autoantibodies against FHL1 were recently discovered in adults with idiopathic inflammatory myopathies (IIMs) and were found to be associated with clinical features and outcomes indicative of increased disease severity. Anti-FHL1 autoantibodies have not been described in children. Here, the prevalence and clinical features associated with anti-FHL1 autoantibodies were examined in a large North American cohort of juvenile patients with IIM. Methods: Sera from 338 juvenile IIM patients and 91 juvenile healthy controls were screened for anti-FHL1 autoantibodies by ELISA. Clinical characteristics and HLA alleles of those with and without anti-FHL1 autoantibodies were compared among those with juvenile IIM. Results: Anti-FHL1 autoantibodies were present in 10.9% of juvenile IIM patients and 1.1% of controls. The frequency of anti-FHL1 autoantibodies among clinical and serologic subgroups did not differ. A higher percentage of Asian patients had anti-FHL1 autoantibodies (11% vs 0.7%; P = 0.002). Myositis-associated autoantibodies (MAAs) [odds ratio (OR) 2.09 (CI 1.03, 4.32)], anti-Ro52 autoantibodies specifically [OR 4.17 (CI 1.83, 9.37)] and V-sign rash [OR 2.59 (CI 1.22, 5.40)] were associated with anti-FHL1 autoantibodies. There were no differences in other features or markers of disease severity. No HLA associations with anti-FHL1 autoantibodies in Caucasian myositis patients were identified. Conclusion: Anti-FHL1 autoantibodies are present in ∼11% of juvenile IIM patients and commonly co-occur with MAAs, including anti-Ro52 autoantibodies. In contrast to adult IIM, anti-FHL1 autoantibodies in juvenile myositis are associated with V-sign rash but not with other distinctive clinical features or worse outcomes.